Rapid inventory, preliminary annotated checklist, and breeding records of the birds (Aves) of the Boanamo indigenous community, Orellana Province, Ecuador. Issue 1 (30th November 2018) - Greeney, Harold F.; Gualingua, Domingo; Read, Morley; Puertas, Cecilia; Evans, Larry; Baihua, Otobo; Killackey, Ryan P.
Abstract: We present the results of a rapid avian inventory conducted September 2012 in the vicinity of Boanamo, within the Territorio Étnico Waorani and Parque Nacional Yasuní, Orellana and Pastaza provinces, Ecuador. Our inventory is the first of its kind from within the Territorio Etnico Waorani, and was carried out using visual and auditory detections made during a 16-day survey. We recorded 362 species of birds during the survey, a number that is around 60% of the expected bird community from this previously unexplored area. We include both qualitative and quantitative natural history information, primarily concerning reproductive behavior, for 41 species.